2004
DOI: 10.1111/j.1465-3435.2004.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Student Involvement in University Life — Beyond Political Activism and University Governance: a view from Central and Eastern Europe

Abstract: Since the 1980s and early 1990s, much attention has focused on the position of students as stakeholders in the process of higher education. The importance of student evaluation is now widely recognised; in many countries, the move toward fee-based funding has increased the power of students as 'consumers' of their education. At the same time, it is often asserted that students are reluctant to participate in university life, concerned primarily (sometimes exclusively) with obtaining their formal qualification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 7 publications
(9 reference statements)
2
19
0
1
Order By: Relevance
“…Due to the heavy demands of engineering programmes, students need to be active in structuring their learning environment, which can be achieved by effectively communicating with their teachers and peers (Bateson and Taylor 2004). Furthermore, learning processes in higher education go further than interaction between students and teachers in the classrooms and lecture theatres (Kuh, Laird, and Umbach 2004;Pascarella and Terenizini 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the heavy demands of engineering programmes, students need to be active in structuring their learning environment, which can be achieved by effectively communicating with their teachers and peers (Bateson and Taylor 2004). Furthermore, learning processes in higher education go further than interaction between students and teachers in the classrooms and lecture theatres (Kuh, Laird, and Umbach 2004;Pascarella and Terenizini 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They also suggested that being involved in social aspects as well as the academic realm retains students and an institution must recognize "that the social dimension in learning activities is critical" (Machado et al, 2011, p. 420). Bateson and Taylor (2004) agreed with this point, suggesting that "the learning process in the university goes beyond classroom interactions between student and professors, reading, writing, and taking examinations" (p. 479) and there must be further effort to address this. Osfield (2008) recognized that there is a "blurring of boundaries" between academics and support in higher education that requires more focus on the co-curriculum and, in turn, develops a need to better understand how and where learning occurs and how it is assessed.…”
Section: Assessing Student Satisfactionmentioning
confidence: 98%
“…Although there has been some effort to assess student satisfaction at European universities, Bateson and Taylor (2004) found that university decision makers only receive sporadic student feedback although it is critical to planning the appropriate implementation of programs. A more systematic and comprehensive effort of assessing student life is prepared every 3 years by the Social and Economic Conditions of Student Life in Europe report, which analyzes the changing trends in European higher education (Orr, Gwoce, & Netz, 2011).…”
Section: Assessing Student Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no induction courses, no personal tutoring and any communication was restricted to notes posted on notice boards. Bateson and Taylor (2004) judge such an approach as leaving students to their own devices, without showing any care or providing support, therefore throwing students into liminal space (Meyer and Land 2006), where traversing the zone of proximal development (Vygotsky 1987), which can be understood as 'the distance between the actual developmental level [. .…”
Section: University Scenario Specific For Cee Countriesmentioning
confidence: 99%